Linear Features of Gravure Print Images - Yılmaz, Ayşegül (Bursa Uludağ University, 2024)
In ancient times, human beings drew lines on stone, soil and mud with bones and horns to transfer their ideas and experiences to the next generations. The first line was applied in history was created by making a groove to leave a mark on a hard surface. Gravure printing (intaglio printing) is the art of carving a hard surface and making patterns with lines and transferring these patterns to paper. Since this printing is done by hand, it is a very different method from press and digital printing. Gravure printings were created by artists so it has high artist value compared to other printing techniques. The techniques and materials used throughout history were developed and changed a lot, thus various engraving techniques emerged. There is no comprehensive study in the literature which examines chronological development of the materials used in gravure printing by considering examples of leading artist and line formations in their prints. For this reason, our article aims to explain the techniques and materials used during the development of engraving art and the forms of the lines. Our study is based on qualitative research method. The data was obtained from books, theses and articles in the literature. The information obtained from the literature reviews was examined using the content analysis method and interpreted logically. First of all, the chronological development of engraving techniques and the materials used in these techniques were investigated. In the light of the information obtained, it has been hypothesized that the materials used in engraving techniques affect the formation of engraving images with different linear features. Within the scope of the study, the wood engraving technique, metal engraving technique and acid etching techniques were explained according to the chronological order in the development of the art of engraving, and the effects of the lines were examined by considering the works of the artists. For wood engraving technique examples of “Thomas Bewick”, for metal graving examples of “Albercht Durer” and for acid etching examples of “Rembrandt van Rijn” were used and lines were analyzed based on their printings. It was observed that, steel pen was often preferred for graving of copper plates because it was easy to apply. Objects on the plates were described full in details with lines. It has been determined that when the pencil was applied vertically, the lines were deep and strong, and when the pencil was applied horizontally, the lines were thinner and superficial. Three-dimensional perception was created with thin and thick lines. Object which was behind the others drown with thin lines and the objects in the front were drown with thicker lines. The ends of the lines that were close to each other were closed from start and end so white line effect was given between the black lines. Light, shadow and volume were created with parallel and diagonal lines. Lines were also created using the acid etching method, but these were more superficial, the boundaries of the objects were removed, and light and shadow gained importance. As a result, in this article, it was shown with examples that lines were formed with different effects due to usage of different engraving techniques.

İnsanoğlu ilk çağ zamanında kemikle ve boynuzla taşa, toprağa ve çamura çizgiler çizip fikirlerini ve tecrübelerini aktarmışlardır. Tarihte ilk uygulanan çizgi sert bir zemin üzerine iz bırakmak için oluk yaparak oluşturulmuştur. Gravür baskı (çukur baskı) da sert bir yüzeyi oyarak çizgilerle desen yapıp bu desenleri kâğıda aktarma sanatıdır. Bu baskı elle yapıldığı için matbaa ve dijital baskıdan çok farklı bir yöntemdir. Tarih boyu kullanılan teknikler ve malzemeler çok değişmiştir böylece çeşitli gravür teknikleri ortaya çıkmıştır. Literatürde gravür baskıda kullanılan malzemeler ve bunların çizgi oluşumundaki etkilerini inceleyen bütünsel bir çalışma bulunmamaktadır. Bu nedenle makalemizde gravür sanatı gelişim süresince kullanılan teknikler malzemeler ile oluşan çizgilerin formlarının açıklanması amaçlanmaktadır. Çalışma kapsamında literatür taramalarından elde edilen bilgiler ışığında gravür sanatının gelişimindeki kronolojik sıralamaya göre ağaç gravür tekniği, metal gravür tekniği ve asitle yedirme teknikleri açıklanıp bu tekniklerin önde gelen sanatçılarının eserleri örnek alınarak çizgilerin etkileri incelenmiştir. Gravürlerde uygulanabilirliği kolay olduğundan sıklıkla bakır levhalar üzerinde çelik kalem tercih edilmiştir. Levhalar üzerinde nesneler çizgilerle tüm ayrıntılarına kadar tanımlanabilmiştir. Kalem, dik uygulandığında çizgilerin derin ve kuvvetli, yatık uygulandığında çizgilerin daha ince ve yüzeysel olduğu tespit edilmiştir. İnce çizgilerle, kalın çizgilerin önünde veya arkasındaymış hissi verilip üç boyut algısı yaratılmıştır. Yakın olan çizgilerin uçları kapatılıp siyah çizgilerin arasına beyaz çizgi efekti verilmiştir. Paralel ve çapraz çizgilerle ışık, gölge ve hacimlendirmeler yapılmıştır. Asitli yedirme yöntemi kullanarak da çizgiler oluşturulmuş ancak bunlar daha yüzeysel, nesnelerin sınırları kaldırılmıştır, ışık ve gölge önem kazanmıştır. Sonuç olarak, bu makalede gravür baskıda farklı teknikler ile grafiksel olarak önem taşıyan çizgilerin farklılıkları ve etkileri açıklanmıştır.
Gravür Baskı Resimlerinin Çizgisel Özellikleri
Keywords: Graphic Design; Grafik Tasarımı